INFLAMMATORY DISEASES IN ADOLESCENT CHILDREN AND THEIR EARLY DIAGNOSIS - Tursunov Feruz O’ktam o`g`li; Allayorov Abbos Dustmuhammedovich; Dustkulova Yulduzkhon Mahamat qizi (TADQIQOTLAR, 2025)
Abstract: Inflammatory diseases are common among children and adolescents and are a serious problem for the health care system. In children of adolescent age, inflammatory processes are often caused by deficiencies of the immune system, infectious diseases or allergic reactions. These diseases require early diagnosis and treatment, because the adolescent organism is in the period of growth and development, and these diseases can lead to long-term complications. Early diagnosis, diagnosis, treatment methods and prevention of inflammatory diseases in children of adolescent age are considered in the article.